ANALISIS DAN PENGEMBANGAN SISTEM INFORMASI GEOGRAFIS RADIO DAN TELEVISI SIARAN PROPINSI JAMBI BERBASIS WEB PADA BALAI MONITOR SFR JAMBI - Bawono, Bimo Adi; Roestam, Rusdianto (Jurnal Manajemen Sistem Informasi, 2019)
The problems that faced by Balai Monitor SFR Kelas II Jambi Office is they have difficulty in locating, identifying and analyzing of radio frequency interference in radio and television broadcasting. This problem caused by their radio and television broadcasting data still on excel form and not yet available a georgraphic information system which show the location and technical data of the radio and television broadcast. The aims of this study are to analyze the needs of geographic information system required by Balai Monitor SFR Kelas II Jambi Office, then design it using UML (Unifed Modeling Language) and develop it in the form of geographic information system webisite using php, maria db, and google map api application. The result of this study is a web-based geographic information system for broadcasting radio and television in Jambi Province, with location search, identification and analysis of frequency interference features that have been successfully tested, so it can be used to deal with problems that have been faced by Balai Monitor SFR Kelas II Jambi Office